2011
DOI: 10.1016/j.apcata.2010.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Strong metal–support interactions on rhodium model catalysts

Abstract: Reactive processes on catalyst surfaces are studied in this work for Rh/metal oxide model systems by means of surface science techniques. Published results in the literature deal with titania, alumina, and silica as support materials and are briefly reviewed. For the present studies Rh/Al 2 O 3 and Rh/TiO 2 model catalysts with about one monolayer Rh coverage are specially prepared and analyzed by ion scattering spectroscopy, X-ray photoelectron spectroscopy, and thermal desorption measurements as main techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 93 publications
2
34
0
Order By: Relevance
“…This is in contrast to Bennett et al 21,26 who showed the layer on Pd to be Ti 2þ -like by using take-off angle variations in XPS, though the effect on CO adsorption 27 was similar to that observed by Linsmeier and Taglauer. 25 Reactivity measurements by Bonanni 28 suggest that high-temperature annealing of Pt on reduced TiO 2 results in the encapsulation of Pt by a reduced titania layer, agreeing with a mechanism proposed by Fu et al…”
Section: Introductionsupporting
confidence: 60%
“…This is in contrast to Bennett et al 21,26 who showed the layer on Pd to be Ti 2þ -like by using take-off angle variations in XPS, though the effect on CO adsorption 27 was similar to that observed by Linsmeier and Taglauer. 25 Reactivity measurements by Bonanni 28 suggest that high-temperature annealing of Pt on reduced TiO 2 results in the encapsulation of Pt by a reduced titania layer, agreeing with a mechanism proposed by Fu et al…”
Section: Introductionsupporting
confidence: 60%
“…The binding energy assignment is in accordance with those in the literature. 4345 As shown in Figure 5a, the binding energies at 307.1/311.8 and 308.1/312.8 eV in Figure 5a can be ascribed to 3d 5/2 /3d 3/2 of metallic Rh and oxidized Rh 3+ species, respectively, while the binding energies at 778.1/793.1 and 780.3/795.8 eV could be assigned to 2p 3/2 /2p 1/2 of Co 0 and Co 3+ species, respectively. 4648 In addition, a broad satellite peak at 783.6/802.0 eV is assigned to 2p 3/2 /2p 1/2 of Co 2 O 3 , suggesting that the Co ions are primarily in a high-spin electronic state.…”
Section: Resultsmentioning
confidence: 99%
“…Yoo et al [47] reported that as Pt NPs size decreases from 6 to 1 nm, there is stronger metalsupport interaction depicted from greater change in the electronic factors that cause the modification of the work function of the catalyst surface. Authors used the potential of zero total charge (PZTC) and in-situ X-ray absorption near-edge structure (XANES) to analyse the electronic states and show that small noble metal NPs in the range of 1.5 nm exhibit much higher changes in the electronic properties, which explains their high activity toward organic molecules oxidation [47][48][49]. Smallest NPs were also found to have higher surface coverage by oxygenated species promoted by TiO 2 than larger NPs [47].…”
Section: Effect Of the Particle Sizementioning
confidence: 95%